Ascites-derived CDCP1+ extracellular vesicles subcluster as a novel biomarker and therapeutic target for ovarian cancer - Kong, Lingnan; Xu, Famei; Yao, Yukuan; Gao, Zhihui; Tian, Peng; Zhuang, Shichao; Wu, Di; Li, Tangyue; Cai, Yanling; Li, Jing (Frontiers in Oncology, 2023)
Ovarian cancer (OVCA) is one of the most prevalent malignant tumors of the female reproductive system, and its diagnosis is typically accompanied by the production of ascites. Although liquid biopsy has been widely implemented recently, the diagnosis or prognosis of OVCA based on liquid biopsy remains the primary emphasis. In this study, using proximity barcoding assay, a technique for analyzing the surface proteins on single extracellular vesicles (EVs), we discovered that the CUB domain-containing protein 1+ (CDCP1+) EVs subcluster was higher in the ascites of OVCA patients compared to benign ascites. For validation, serum and ascites samples from patients with epithelial ovarian cancer (EOC) were collected, and the level of CDCP1 was considerably elevated in the ascites of OVCA patients by enzyme-linked immunosorbent assay. Consequently, the overall survival and disease-free survival of the group with high CDCP1 expression in EOC were significantly lower than those of the group with low expression. In addition, the receiver operating characteristic curve demonstrates that EVs-derived CDCP1 was a biomarker of early response in OVCA ascites. Our findings identified a CDCP1+ EVs subcluster in the ascites of OVCA patients as a possible biomarker for EOC prevention.